Kontribusi KepemimpinanKompensasi Dan Lingkungan Kerja Dalam Peningkatan Kinerja Direktorat Reserse Dan Kriminal Khusus POLDA SULSELBAR - Mashur Razak; Muhammad Hidayat; Japaruddin Japaruddin (AkMen JURNAL ILMIAH, 2022)
This research is intended to analyze the influence of leadership, compensation and work environment on the performance of personnel of the Directorate of Investigation and Special Crimes of POLA West Sulawesi using a quantitative approach. The sample of this study was all members of the Directorate of Investigation and Special Crime of the West Sulawesi Regional Police, the data of this study were analyzed using multiple linear regression analysis with a hypothesis test tool partially using the t test and simultaneously using the f test. The results showed that leadership, compensation and work environment have a positive and partial significant effect on performance, simultaneous hypothesis testing also proves that compensation leadership and work environment together have an effect on performance